Struktura zadaniowa jako element organizacji dynamicznej - Lichtarski, Janusz M. (The task structure as the element of dynamic organization, 2006)
The article presents task structure (project structure) as the organizational form of a dynamic organization. Literature studies of many modern concepts and models of organizational structures were carried out. The text is also based on the empirical research performed in 2005 in 131 enterprises, dedicated to identification of selected elements of modern (organic) structures in management practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 106-116